Faktor yang Berhubungan dengan Pemilihan Kontrasepsi Tubektomi Wanita Usia Subur - Istri Utami; Efi Trimuryani (Jurnal Keperawatan Silampari, 2020)
The purpose of this study was to determine the factors associated with the selection of tubectomy contraception in women of childbearing age. The type of this research is an analytic survey with a cross-sectional approach. The results of the study of 72 female respondents of childbearing age showed that the factor that was proven to be related to the choice of tubectomy contraception was Parity (p = 0.021). While the unrelated factors are Age (p = 0.732), Education (p = 0.896), and Knowledge (p = 0.086). In conclusion, the factors that have been proving to be related to the choice of tubectomy contraception is parity, whereas unrelated factors are age, education, and knowledge. Keywords: Contraception, Tubectomy, Fertile Age Women